Síntese e caracterização de nanopartículas de quitosana carreando curcumina para avaliação de inativação fotodinâmica - Laís Fernandes Aguilera (2024)
For a long time, humanity has faced several diseases caused by bacterial infections. The discovery of antibiotics completely changed modern medicine and extended human life expectancy. However, abuse and misuse of antibiotics over the years is one of the factors that leads to bacterial resistance reaching alarming levels. The development of a new generation of anti-infective medicines using natural antimicrobial products is very promising. Another promising strategy to eradicate microorganisms is photodynamic inactivation (PDI). In view of this, the present work aimed to synthesize and characterize chitosan nanoparticles (NPs) carrying curcumin (Cur NPs) to evaluate their effectiveness in the photodynamic inactivation (PDI) process. Cur NPs were characterized by atomic force microscopy, dynamic light scattering and Zeta potential. Furthermore, Cur-NPs achieved an encapsulation efficiency of 96%, and a slower release compared to free curcumin. To carry out the biological tests, the strains Staphylococcus aureus (ATCC 25923) and Escherichia coli (ATCC 25922) were used. They were divided into two groups: (I) irradiated group and (II) non-irradiated group. The NPs internalization time was 1 hour. The irradiated groups of both strains were subjected to 1 hour of illumination with LED light, at a wavelength of 450 nm (blue) and an energy dose of 28.84 mW.cm-2. The concentrations of NPs Cur, 0.02 mg.mL-1; 0.04 mg.mL-1; 0.08 mg.mL-1; Polaxamer 407 at 25 mg.mL-1 and Chitosan + TPP at 1 mg.mL-1 for IFD were tested. To perform morphological analyzes of the strains after IFD, scanning electron microscopy (SEM) and Transmission Electron Cryomicroscopy (Cryo-ME) images were obtained. To evaluate the production of reactive oxygen species (ROS), the fluorescent marker dihydroethidium (DHE) was used and the production of ROS was monitored over time. Cur NPs showed photodynamic effects for the two strains tested, as well as inducing bactericidal effects at the highest concentrations tested. The SEM and Cryo-ME results showed that IFD promoted morphological changes in the structures of bacterial cell walls, lysing the cells. The results obtained indicate that Cur NPs have the potential for photoinactivation of bacteria and that these results are directly related to the production of ROS. Key words: nanoparticles, chitosan, curcumin, photodynamic inactivation, bacteria.